2017
DOI: 10.1016/j.rser.2017.03.135
|View full text |Cite
|
Sign up to set email alerts
|

The application of microwave heating in bioenergy: A review on the microwave pre-treatment and upgrading technologies for biomass

Abstract: Bioenergy, derived from biomass and/or biological (or biomass-derived) waste residues, has been acknowledged as a sustainable and clean burning source of renewable energy with the potential to reduce our reliance on fossil fuels (such as oil and natural gas). However, many bioenergy processes require some form of pre-treatment and/or upgrading procedure for biomass to generate a modified residue with more suitable properties and render it more compatible with the specific energy conversion route chosen. Many o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 248 publications
(95 citation statements)
references
References 195 publications
(222 reference statements)
0
75
0
3
Order By: Relevance
“…The high temperature could accelerate the chemical reaction, and showed up as the increased weigh loss rate at the corresponding temperature range. When microwave was applied to biomass components, swelling and fragmentation effects occurred within the materials and changed the structure disruption of the polymers, which resulted in the change of dielectric properties . In general, the absorbed power for material was proportional to the dielectric loss factor, and the temperature increased as both the dielectric constant and dielectric loss factor increased for all samples measured .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The high temperature could accelerate the chemical reaction, and showed up as the increased weigh loss rate at the corresponding temperature range. When microwave was applied to biomass components, swelling and fragmentation effects occurred within the materials and changed the structure disruption of the polymers, which resulted in the change of dielectric properties . In general, the absorbed power for material was proportional to the dielectric loss factor, and the temperature increased as both the dielectric constant and dielectric loss factor increased for all samples measured .…”
Section: Resultsmentioning
confidence: 96%
“…Among various pyrolysis processes, microwave heating (MH) is a promising technology used for biomass conversion with the advantages of rapid, volumetric and selective heating, which could reduce the limitations of heat transfer with conventional heating (CH), and offer high heating rates with a reduced process time. The most important advantage of microwave‐assisted pyrolysis (MAP) is that the pyrolysis can occur at relatively lower temperatures and with a lower activation energy compared to conventional pyrolysis (CP), which means less reaction limitation and energy consumption . The MAP of wheat straw for hydrocarbons took place at reduced temperatures with the release of bio‐gases at 120–180°C, compared with CP at 250–400°C to achieve the same gas composition .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment processes based on steam explosion, ammonia fiber/freeze explosion, ammonia recycle percolation, hydrothermolysis, milling, microwave irradiation, electron beam irradiation, and pretreatments with alkalis, acids, supercritical carbon dioxide, lime, white rot fungi, peroxide and organic solvents (organosolvolysis) have been extensively investigated 4) ,21) 23) . Microwave irradiation or heating is expected to provide an alternative and reliable option to conventional pretreatment systems based on the use of different chemistry due to the internal heating, and rapid heating rates up to the target temperature 22) . Numerous studies on pretreatment of various raw materials have been reported 24) 30) .…”
Section: Pretreatmentmentioning
confidence: 99%
“…3, is also an important required preprocessing step to improve the net energy balance of bioenergy production. Reduction of water content from raw materials both reduces weight directly, and critically affects the energy efficiency of subsequent biomass processing, quality of products, and longevity of the product shelf life 22) . Microwave drying is also an effective energy-saving method.…”
Section: Dryingmentioning
confidence: 99%